A Linear Regression Modeling Analysis of the Energy, Water, and Chemical Consumption in the Operating Configuration at 740 MW Priok Combined Cycle Power Plant - Muhammad, Raihan; Rahman, Arief; Jamil, Muhamad Fauzi (Journal of Mechanical Design and Testing, 2024)
In realizing efficient energy use, the Government of Indonesia has issued a National Energy Policy in Government Regulation (Peraturan Pemerintah) No. 70 of 2009 concerning Energy Conservation, PT PLN Indonesia Power Priok Unit has carried out efficient operational activities. Therefore, to support the company's sustainability and operational performance, especially in terms of efficiency and operational activities, it is necessary to evaluate the process of energy use. The Combine Cycle Power Plant (CCPP) has several operating configurations according to the gas turbine, heat recovery steam generator (HRSG), and steam turbine amount. CCPP Priok Blok 3 operates full-block 2-2-1 or half-block 1-1-1, which means one gas turbine, HRSG, and steam turbine. This configuration of operation impacts the use of energy, water, and chemicals. For this reason, this project aims to model the use of energy, water, and chemicals using linear regression to determine which operating configurations are highly effective in using energy, water, and chemicals. The result of this linear regression modeling is that at the peak load, operation GT2 (gas turbine 2) is more energy efficient, 1.93% more efficient than GT1, than GT1 (gas turbine 1). At the minimum load, GT1 is 9.36% more energy efficient than GT2. At the same time, the water consumption of GT2 is 35.01% more efficient than that of GT1.